IMPACT OF GREEN SUPPLY CHAIN MANAGEMENT PRACTICES ON FIRM’S PERFORMANCE IN MALAYSIA MANUFACTURING INDUSTRY - Rakiman, Umol Syamsyul; Tham , Pei Chee; Rasi, Raja Zuraidah; Wan Mohamad, Wan Maisara; Masri, Hanis Marhainis (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Sustainability is the focus of many manufacturers, yet uncertainty of competitive advantage that can be gained from sustainability causes manufacturer flinches from implementing green supply chain management. This research focuses to examine the implementation level of green supply chain management practices among manufacturing industry in Malaysia. The relationship between green supply chain management practices and operational performance also being studied in this research to show the competitive advantage that can be gained by firm. The green supply chain management that is covered in this study is internal green supply chain management, green supply chain management with suppliers and green supply chain management with customers. Furthermore, the operational performance of firm is identified through product quality, operational flexibility, delivery time and production cost. There are 111 respondents who work in manufacturing industry certified of ISO 14001, answered the questionnaire that send through email. The data is analysed through Software of IBM Statistical Package for Social Science (SPSS). The result showed that there is high implementation level of internal green supply chain management practices while for the external green supply chain management practices are having medium implementation level. Furthermore, the green supply chain management practices have significant and positive relationship with the operational performance. Therefore, implementation of green supply chain management practices helps the manufacturer obtain competitive advantage via better operational performance together with achieving sustainable development.